MENGUJI DETERMINASI KARAKTERISTIK AUDITOR ATAS KUALITAS AUDIT - Sujarwo Sujarwo (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2020)
Providing quality financial reports is a moral obligation of the company. That is, as an ethical effort by management to present good corporate governance. Of course, the underlying reason is the purpose of the organization, why? This method is believed to affect the value of the company in the capital market. Therefore, this study was conducted to review the auditor's determination of audit quality. The sample in this research is 7 KAP in Banten Province by using convinience sampling method with respondent as much as 71 auditor and the questionnaire which returned as many as 69 respondents so that the questionnaire can be processed as much as 69 respondents. Data collection techniques were conducted using questionnaires. Data analysis collected using Statistical Product and Service Solution (SPSS). Data analysis used is data quality test, classical assumption test, regression model test (f test), correlation test, coefficient of determination test (R2), multiple linear regression test, and hypothesis test. The results of the study confirm that Professional Skepticism, Locus of Control, and Independence are factors that have a strong influence on audit quality. This confirms the theory that the auditor's personality role is the key word for quality audit results. Keywords: Professional Skepticism, Locus Of Control, Audit Quality, Independence